The Goldmark Case : An American Libel Trial - Dwyer, William L. (Book collections on Project MUSE., 1984)
The lawyer for the plaintiff describes the 1963 libel case of Washington State legislator John Goldmark--accused of being a communist--and probes the impact of this case on issues of civil liberties, communism and McCarthyism, the radical right, and trial by jury.